"Living Well with Chronic Pain": Integrative Pain Management via Shared Medical Appointments. Issue 1 (4th February 2021) - Znidarsic, Josie; Kirksey, Kellie N; Dombrowski, Stephen M; Tang, Anne; Lopez, Rocio; Blonsky, Heather; Todorov, Irina; Schneeberger, Dana; Doyle, Jonathan; Libertini, Linda; Jamie, Starkey; Segall, Tracy; et al.
Abstract: Objective: To evaluate the effectiveness of a multidisciplinary, nonpharmacological, integrative approach that uses shared medical appointments to improve health-related quality of life and reduce opioid medication use in patients with chronic pain. Design: This is a retrospective, pre–post review of "Living Well with Chronic Pain" shared medical appointments (August 2016 through May 2018). Setting: The appointments included eight 3-hour-long visits held once per week at an outpatient wellness facility. Subjects: Patients with chronic, non–cancer-related pain. Methods: Patients received evaluation and evidence-based therapies from a team of integrative and lifestyle medicine professionals, as well as education about nonpharmacological therapeutic approaches, the etiology of pain, and the relationship of pain to lifestyle factors. Experiential elements focused on the relaxation techniques of meditation, yoga, breathing, and hypnotherapy, while patients also received acupuncture, acupressure, massage, cognitive behavioral therapy, and chiropractic education. Patients self-reported data via the Patient-Reported Outcomes Measurement Information System (PROMIS-57) standardized questionnaire. Use of opioid medications was evaluated in morphine milligram equivalents. Results: A total of 178 participants completed the PROMIS-57 questionnaire at the first and the last visits. Statistically significant improvements in all domains (Physical Functioning, Anxiety, Depression, Fatigue, Social Roles, Pain Interference, and Sleep Disturbance) were observed ( P  < 0.001) between the pre-intervention (visit 1) and post-intervention (visit 8) scores. Average opioid use decreased nonsignificantly over the 8-week intervention, but the lower rate of opioid use was not sustained at 6 and 12 months' follow-up. Conclusions: Patients suffering from chronic pain who participated in a multidisciplinary, nonpharmacological treatment approach delivered via shared medical appointments experienced reduced pain and improved measures of physical, mental, and social health without increased use of opioid pain medications.